Research and Analysis of Mobility Enhancement in Small Cell - Dongjun Wang; Yuanke Fu; Lun Tang; Qianbin Chen (Dianxin kexue)
Small cell network is a multi-layer cell network formed by low-power nodes whose base stations transmit power is lower than conventional macrocell base stations. More and more industry attention is pained to the development of small cell which is considered as an important part of LTE-Advanced technology study. The performance of a variety of mobile state estimation scheme in mobility management was analyzed and evaluated and the same work was done on the protection scheme of the switching instruction involved in a cellular switch. A summary was made about challenge and future research directions of small cell mobility management finally.